Conceptually expanding the curricular alignment model to understand the coherence of the graded summative assessment practices of teachers: issues and perspectives - Pasquini, Raphaël (Mesure et évaluation en éducation, 2019)
Curricular alignment refers to the links of coherence, found in any teaching-learning process, between curriculum objectives, learning tasks and assessment approaches. This model makes it possible to understand the coherence of any assessment approach. By mobilizing data from a collaborative study carried out on eight secondary school teachers of mathematics and French, we will show, however, that its meaning is rather limited when it comes to understanding coherence in graded summative assessment practices and that, consequently, the model needs to be expanded conceptually. To this end, we will draw on an example of a summative test modelled in this way. Our findings demonstrate the relevance of analyzing summative assessment practices with the help of the expanded model, while considering the role that context plays in certain of its aspects.